Treatment outcomes and tolerability of the revised WHO anti-tuberculosis drug dosages for children - Nansumba, Margaret; Kumbakumba, Elias; Orikiriza, Patrick; Bastard, Mathieu; Mwanga, J. A.; Boum, Yap; Debeaudrap, Pierre; Bonnet, Maryline (The International Journal of Tuberculosis and Lung Disease, 2018)
BACKGROUND: In 2010, the World Health Organization (WHO) revised the paediatric dosages of anti-tuberculosis drugs, increasing rifampicin to 15 mg/kg, isoniazid to 10 mg/kg and pyrazinamide to 35 mg/kg. We assessed treatment outcomes, safety and adherence among children treated with the new recommended dosages. METHODS : Prospective cohort of children started on anti-tuberculosis treatment in Uganda with 12 months of follow-up, including alanine aminotransferase (ALT) monitoring. Treatment intake was observed. RESULTS : Of 144 treated children, 81 were male (56.3%), 106 (73.6%) were aged,5 years, 30 (22%) had moderate to severe malnutrition and 48 (33.3%) had human immunodeficiency virus infection. Treatment outcomes were as follows: 117 (81.3%) successes, 3 (2.1%) failures, 4 (2.8%) lost to follow-up, 19 (13.2%) deaths and 1 (0.7%) transferred out. There was no relapse. Severe malnutrition (adjusted hazard ratio 8.76, 95% confidence interval [CI] 1.59-48.25) was the only predictor of death. Two serious adverse events were attributed to treatment: one case of increased ALT and one with peripheral neuropathy. Median ALT values at baseline and at weeks 2, 4 and 8 were respectively 24 (interquartile range [IQR] 16-39), 26 (IQR 18-38), 28 (IQR 21-40) and 27 (IQR 19-38) international units/l. Treatment adherence was above 85% on all visits. CONCLUSION: We confirm the good tolerability of and adherence to the new treatment recommendations. The increased risk of fatal outcome among severely malnourished children requires attention.
Keywords: OUGANDA; children; mortality; treatment; tuberculosis